Characterizing Radiation Effectiveness in Ion-Beam Therapy Part II: Microdosimetric Detectors - Colautti, Paolo; Magrin, Giulio; Palmans, Hugo; Cortés-Giraldo, Miguel A.; Conte, Valeria (Frontiers in Physics, 2020)
The specific advantages of ion beams for application in tumor therapy are attributed to their different macroscopic and microscopic energy deposition pattern as compared to conventional photon radiation. On the macroscopic scale, the dose profile with a Bragg peak at the highest depths and small lateral scattering allow a better conformation of the dose to the tumor. On the microscopic scale, the localized energy deposition around the trajectory of the particles leads to an enhanced biological effectiveness, typically expressed in terms of clinically significant relative biological effectiveness (RBE). Experimental investigations reveal complex dependencies of RBE on many physical and biological parameters, as e.g. ion species, dose, position in the field, and cell or tissue type. In order to complement the experimental work, different approaches are used for the characterization of the specific physical and biological properties of ion beams. In a set of two papers, which are linked by activities within a European HORIZON 2020 project about nuclear science and application (ENSAR2), we describe recent developments in two fields playing a key role in characterizing the increased biological effectiveness. These comprise the biophysical modelling of RBE and the microdosimetric measurements in complex radiation fields. This second paper focuses on microdosimeters and on the importance of providing the instrumental measurement of the spectra of the imparted energy. The relevance of microdosimetric quantities, complementary to the absorbed dose is emphasized. This parts provides an overview of the microdosimetric concepts and the recent experimental developments in the field of microdosimetry applied to ion beam therapy. Finally, a non-exhaustive, dedicated section in included to emphasize the relevance of Monte Carlo simulations as tool for the design of the microdosimetric detectors and for the interpretation of the experimental results. For the two distinctive clinical beams of protons and carbon ions, the lineal-energy parameters are correlated to the clinical concept of Linear Energy Transfer (LET) and RBE. The possibilities of applying experimental microdosimetry in ion-beam therapy are discussed considering the consolidated irradiation characteristics as well as the most recent developments.